Conferência de Aparecida - Libanio, João Batista (Revista Eclesiástica Brasileira, 2007)
Documentos e acontecimentos prévios ofereceram o eixo central da Conferência: seguimento de Cristo e missão. Bento XVI traçou-lhe algumas pautas. Com o método ver-julgar-agir, trabalhou-se em grupo. Em discurso próprio do magistério eclesial, o Documento se estruturou em torno do eixo da realidade na perspectiva da fé de ser discípulo e missionário de Cristo para chegar a um agir pastoral, revelando continuidades, rupturas e novidades em relação às conferências anteriores. Abstract: Previous documents and events – in particular, those related to the following of Christ and the mission – provided the central axle for the Conference. Bento 16th drew some of its agendas. Using the seeing-assessing-acting methodology, organizers worked in teams. Following the distinctive discourse of the ecclesial magisterium, the Document was structured around the axle of reality, within the perspective of the faith of being a disciple and a missionary of Christ in order to achieve a pastoral action. It also compared the present Conference with previous ones, in terms of continuities, ruptures and innovation.